The Origin-Affiliation effect on Dialect Maintenance - Mahmoud Mamdouh Baker Nassar,; Mohammad Shatanawi, (Technium Social Sciences Journal, 2020)
This paper aims at finding out if the Syrian refugees' dialect in Irbid is in a process of maintenance or in a process of being transformed or modified. In this paper, the data were collected via a questionnaire, interviews, and recording for some meetings. The study investigates the Syrian dialect use, domain, and the Syrians attitude toward their dialect. The results indicate that the Syrians are in the process of maintaining their dialect.